Laser-induced incandescence of silicon surface under 1064-nm excitation - Kopyshinsky, A.V.; Zelensky, S.E.; Gomon, E.A.; Rozouvan, S.G.; Kolesnik, A.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
Laser-induced incandescence (LII) of silicon surface is investigated under the excitation by a Q-switched YAG:Nd laser. With the increase of laser irradiation dose, the increase of LII signal is observed, which is attended by visible changes of the surface geometry. The anomalous behavior of the parameter of non-linearity of LII is observed with the increase of laser excitation power.